A comprehensive overview of ovarian cancer stem cells: correlation with high recurrence rate, underlying mechanisms, and therapeutic opportunities - Hadi Alizadeh; Parastoo Akbarabadi; Alireza Dadfar; Mohammad Reza Tareh; Bahram Soltani (Molecular Cancer)
Abstract Ovarian cancer is one of the most lethal gynecological malignancies, with a recurrence rate of 70–80%, particularly in patients diagnosed at advanced stages (stage III or IV), where the five-year survival rate falls below 30%. A key driver of this recurrence is the presence of cancer stem cells (CSCs), which exhibit resistance to chemotherapy and possess the capacity for self-renewal, plasticity, and tumor regeneration. The tumor microenvironment (TME) plays a crucial role in maintaining ovarian cancer stem cells (OCSCs) by providing nutrient and oxygen gradients, extracellular matrix (ECM) interactions, immune cell modulation, and support from cancer-associated fibroblasts (CAFs). CAFs secrete growth factors, cytokines, and ECM components that create a pro-tumorigenic niche, promoting CSC maintenance, invasion, and chemoresistance. Additionally, dysregulation of critical signaling pathways, including WNT, NOTCH, PI3K/AKT/mTOR, TGF-β, JAK/STAT, Hedgehog, NF-κB, and Hippo, supports CSC stemness, plasticity, maintenance, and adaptability, thereby increasing their survival and progression. Numerous inhibitors targeting these pathways have shown promise in preclinical studies. This review discusses the molecular mechanisms underlying CSC-mediated recurrence in ovarian cancer and highlights emerging therapeutic strategies. Particular emphasis is placed on the potential of combination therapies involving routine platinum or taxane based regimens with OCSC inhibitors to overcome chemoresistance, reduce recurrence rates, and improve survival outcomes for patients with advanced-stage ovarian cancer. Graphical Abstract